Effectiveness of Think-Pair-Square Strategy on Students’ Reading Comprehension - Warno Edi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
This research is about the effects of Think-Pair-Square (TPR) strategy on the reading comprehension of Seventh grade students’ at SMPN 16 Batam. It is purpose to find out the effect of TPR strategy on the reading comprehension. To achieve the objectives of the research, the researcher conducted experimental research. This experimental research was held at SMPN 16 Batam. The population in this research is all students of eight grade students at SMPN 16 in academic year 2014/2015. The researcher conducted research in one class. The first class is (VII.4) was as experimental class. The experimental class was taught reading descriptive text using TPR strategy. In analyzing the data, the researcher used a quantitative measurement to find the result. The analysis of the data showed that there was a significant difference of the students’ achievement before conducted treatment 62.17 for experimental class. The average of the students’ achievement after conducted treatment in experimental class was 87.33. The implication of this research seems to be applicable for seventh grade students. This strategy encouraged the students to be more active during the learning process. The suggestion is the students should know about this strategy. It will make easier while learning if they understand about the rule and procedure. To the other research, the researcher expects to understand well about this strategy in order to make easy for doing further research. Based on this finding, it can be concluded that the use of TPR strategy give significant effect in reading comprehension than the use of other conventional method.Keywords: TPR strategy, reading comprehension, experimental research